2013
DOI: 10.5271/sjweh.3408
|View full text |Cite
|
Sign up to set email alerts
|

Associations of traffic noise with self-rated health and psychotropic medication use

Abstract: This study shows that road traffic noise >60 dB (compared to <45 dB) was associated with poor self-rated health in men, but not in women. This association was stronger among men with high trait anxiety scores. Noise levels were not associated with psychotropic medication use. Affiliation 235Original article Scand J Work Environ Health. 2014;40(3):235-243. doi:10.5271/sjweh.3408 Associations of traffic noise with self-rated health and psychotropic medication useby Jaana I Halonen, PhD, 1 Timo Lanki, PhD, Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Another research deployed by Halonen et al . () in Finland noted down that road traffic noise is a general environmental inconvenience and it has been known to spread the danger of many kinds of health issues. Their work analysed whether transportation noise is correlated with self‐assessed health, the outcomes indicating that noise level over 60 decibels was connected to poor self‐assessed health for male respondents with no relationship being determined among female respondents.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another research deployed by Halonen et al . () in Finland noted down that road traffic noise is a general environmental inconvenience and it has been known to spread the danger of many kinds of health issues. Their work analysed whether transportation noise is correlated with self‐assessed health, the outcomes indicating that noise level over 60 decibels was connected to poor self‐assessed health for male respondents with no relationship being determined among female respondents.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, sleep medication use may be an indicator of sleeping problems. Previous studies in the field of environmental epidemiology have used various medications as the outcome including antihypertensives, antiasthmatics, and psychotropic medications including sleep medications and anxiolytics . In these studies, the medication use has either been self‐reported or drawn from a prescription registry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the field of environmental epidemiology have used various medications as the outcome including antihypertensives, [2][3][4] antiasthmatics, 3 and psychotropic medications including sleep medications and anxiolytics. [3][4][5][6][7][8] In these studies, the medication use has either been self-reported or drawn from a prescription registry. Self-reported medication use has typically been collected via postal questionnaires or phone interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are strong indications of an association between traffic noise and sleep disturbances, studies on the association between road traffic noise and sleep medication use are scarce. In previous studies of noise and sleep medication use, the medication use has either been reported subjectively [ 10 , 18 , 19 ] or been drawn from a registry recording individual purchase of medications [ 20 , 21 ]. The registry based studies have, however, not exclusively studied sleep medication use, but have also included other types of medication such as antidepressants and anxiolytics.…”
Section: Introductionmentioning
confidence: 99%